Dividend Payout Ratio, Free Cash Flow, and Share Repurchases in Indonesian Listed Companies - Hidayatun Lisa; Zuraida Zuraida (Jurnal Akuntansi dan Bisnis, 2023)
The primary objective of this research is to examine the impact of the dividend payout ratio and free cash flow on share repurchases in Indonesian companies listed on the Indonesia Stock Exchange between 2016 and 2020. The study focuses on companies that engaged in share repurchases during the specified period. A purposive sampling technique was employed, resulting in a sample size of 36 share repurchase instances for the purpose of analysis. The financial statements of these companies were utilized as the data source, and a multiple linear regression analysis was conducted. The results of the study reveal a significant positive relationship between both the dividend payout ratio and free cash flow and share repurchases. Tujuan dari penelitian ini adalah untuk menganalisis pengaruh dividend payout ratio dan free cash flow terhadap share repurchases pada perusahaan yang tercatat di Bursa Efek Indonesia selama periode 2016-2020. Populasi dalam penelitian ini terdiri dari perusahaan yang terdaftar di Bursa Efek Indonesia yang melakukan pembelian kembali saham selama periode penelitian. Sampel penelitian ini terdiri dari 36 kegiatan pembelian kembali saham yang dilakukan selama periode penelitian. Data dalam penelitian ini dikumpulkan dari laporan keuangan perusahaan dan dianalisis menggunakan regresi linear berganda. Temuan dari penelitian ini menunjukkan adanya pengaruh positif dan signifikan baik dari rasio pembayaran dividen maupun arus kas bebas terhadap pembelian kembali saham.